Biological prerequisites for the development of correctional and preventive measures for young basketball players with different types of posture - Nevolin , Dmytro (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. According to numerous studies, the problems of functional disorders of the musculoskeletal system of children and young people have also not escaped the practice of sport. Experts attribute these disorders to the trends in modern sport, which include intensification of training loads and lowering the age limit at the initial stage of athletes’ training. There is evidence that functional disorders of the musculoskeletal system in childhood pose a major health threat if they are not detected in a timely manner and measures are not taken to eliminate them. The purpose of the study is to identify the key factors that have the most significant impact on the physical development and physical preparedness of basketball players aged 9 and 10 with different types of posture as a prerequisite for the development of correctional and preventive measures. Research methods: theoretical analysis and synthesis of literary sources; pedagogical observation. Medical and biological research methods (anthropometry, photography and posture analysis); pedagogical experiment; pedagogical testing, pedagogical experiment, methods of mathematical statistics. The experiment involved 66 basketball players aged 9-10 from the Ivano-Frankivsk Children’s and Youth Sports School, after obtaining their parents’ consent to analyse data from their medical records. The research was conducted in compliance with the requirements of the World Medical Association’s Declaration of Helsinki “Ethical principles for medical research involving human subjects”. The results. To study the key factors that have the most significant impact on the physical development and physical preparedness of basketball players aged 9 and 10 with different types of posture, we conducted a factor analysis. This analysis was based on data collected from six groups of participants. Three of them are 9-year-old athletes with normal posture, scoliotic posture and stooped back (12 people in each group), and three groups of 10-year-old basketball players with the same types of posture (10 people in each group). The basis for this analysis was the intercorrelation matrix, which included 16 indicators selected for the presence of relationships with a sufficient degree of intensity in the matrices in these groups. These are somatometric and somatoscopic indicators of physical development, as well as the results of physical preparedness tests. Conclusions. As a result of the factor analysis, the different groups revealed structures consisting of 3, 4 or 5 factors, most of which turned out to be bipolar, where one pole contains indicators pointing to a direct relationship between the studied manifestations, while the other pole contains indicators characterising their opposite expression. All the signs clearly correlate with a high factor load with only one of the factors. Most of the attributes for other factors have insignificant factor loadings, i.e. the resulting factor structures are quite simple and understandable for interpreting the factors.